Welfare Implications of HDB Policy on the Public Housing Price Gradient - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 1989)
In Singapore, extensive government intervention in the housing market has resulted in much deviation from assumptions made in the simple neoclassical urban models. The monocentric model of urban structure is extended to incorporate a subsidized public housing market in which the government-determined price gradient is flatter than the private housing price gradients. The propositionthat the utility of public housing households varies inversely with residential location distance from the CBD is empirically tested by estimating net returns to public housing using resale market data. It was found that net returns decreased with distance from the CBD.